PENGARUH PERSENTASE PENDUDUK MISKIN,PENGANGGURAN TERBUKA TERHADAP PERTUMBUHAN EKONOMI, PENGELUARAN PEMERINTAH SEBAGAI VARIABEL MODERASI DI PROVINSI KALIMANTAN TIMUR - Mahrus Sholeh (AL-MUJADDID - JURNAL EKONOMI DAN BISNIS ISLAM, 2025)
This study aims to explain the existence of economic growth by using the variable percentage of poor population, open unemployment with government spending as a moderating variable. In this study using secondary data published by the Statistics Agency and Bank Indonesia. The data used is annual data from 2017-201. The tools used by SPSS, using the T test and MRA. The results of the study show that the percentage of poor people has no effect on economic growth in East Kalimantan Province. Open unemployment has a significant positive effect on economic growth in East Kalimantan. Government spending is able to moderate the percentage of poor people and open unemployment in East Kalimantan Province.